PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI: Studi Empirik pada SKPD Kabupaten Demak - Andelina, Mis Widya; Hariyanto, Agus (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
The purpose of this study is to know the efforts undertaken by theGovernment of Demak Regency to obtain unqualified opinion. These effortsneed to be appreciated by the local Government Apparatus. TheGovernment's aim is to improve the reliability of the quality of the resultingfinancial statements, particularly in terms of asset management.The selected sample is 141 respondents with purposive samplingtechnique in Demak Regency. Data were obtained by distributingquestionnaires. The questionnaire returned as many as 138 questionnaires.Data analysis using Moderated Regression Analysis (MRA) using ProgarmSPSS.The results showed that the application of local financialaccounting system has a positive effect on the quality of financial statements,while the competence of human resources negatife affect the quality offinancial statements. Similarly, adding organizational commitment as amoderating variable, the application of local financial accounting system hasnegatife influence on the quality of financial statements and human resourcescompetence have a positive effect on the quality of financial statements.